Compare encryption performance across devices to ensure the security of the IOT - A.YU. Pyrkova; ZH.E. Temirbekova (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The internet of things (IoT) combines many devices with various platforms, computing capabilities and functions. The heterogeneity of the network and the ubiquity of IoT devices place increased demands on security and privacy protection. Therefore, cryptographic mechanisms must be strong enough to meet these increased requirements, but at the same time they must be effective enough to be implemented on devices with disabilities. One of the limited devices are microcontrollers and smart cards. This paper presents the performance and memory limitations of modern cryptographic primitives and schemes on various types of devices that can be used in IoT. In this article, we provide a detailed assessment of the performance of the most commonly used cryptographic algorithms on devices with disabilities that often appear on IoT networks. We relied on the most popular open source microcontroller development platform, on the mbed platform. To provide a data protection function, we use cryptography asymmetric fully homomorphic encryption in the binary ring and symmetric cryptography AES 128 bit. In addition, we compared run-time encryption and decryption on a personal computer (PC) with Windows 7, the bluetooth low energy (BLE) Nano Kit microcontroller, the BLE Nano 1.5, and the smartcard ML3-36k-R1.